‎Distinguishing index of Kronecker product of two graphs - ‎Saeid Alikhani; Samaneh Soltani (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2021)
The distinguishing index D'(G) of a graph G is the least integer d such that G has an edge labeling with d labels that is preserved only by a trivial automorphism. The Kronecker product G x H of two graphs G and H is the graph with vertex set V(G) x V(H) and edge set (u,x), (v,y) |u,v ∈ E(G) and x,y ∈ E(H). In this paper we study the distinguishing index of Kronecker product of two graphs.